Investigation of Woody Species Structure and Regeneration Status in the Central Rift Valley, Sidama Regional State, Ethiopia - Assegid Assefa; Tamrat Bekele; Sebsebe Demissew; Tesfaye Abebe (International Journal of Forestry Research)
Protected areas are the most commonly used tool for in situ conservation of biodiversity. Selective removal of species proposed by the local communities living surrounding the national park and grazing pressure negatively affect the composition, structure, and regeneration of woody species. Assessment of vegetation structure and regeneration status of woody species is essential for orienting management activities. The purpose of this study was to investigate the floristic composition, population structure, and regeneration status of woody species in the Loka Abaya National Park, to design conservation strategies. A total of 99, 20 m × 20 m quadrats were systematically laid along an established line transect to collect a list of woody species, abundance, height, and diameter at breast height (DBH), while five 3 m × 3 m subquadrats within the main quadrats were established to assess the regeneration status of woody species. In each quadrat, all woody species were identified, counted, and recorded. In each quadrat, all tree and shrub species higher than ≥2 m in height and ≥2 cm in diameter at breast height were measured by a calibrated wooden stick and by a caliper, respectively. Density, frequency, basal area, importance value index (IVI), height, and diameter at breast height (DBH) were used for description of vegetation structure, while the density of mature trees, saplings, and seedlings was used for assessment of regeneration status of woody species. A total of 101 woody plant species representing 40 families in 69 genera were collected, identified, and documented. Fabaceae was the most diverse family representing 16 (15.84%) species, followed by Euphorbiaceae 9 species (8.91%) and Anacardiaceae with 6 species (5.94%). Four families including Combretaceae, Moraceae, Olacaceae, and Tiliaceae were represented by 4 species each. 4 families were also represented by 3 species each, 12 families were represented by two species each, and 18 families were represented by one species. The density of trees was 831.31 individuals ha−1, while the total basal area was 73.18 m2·ha−1. D. angustifolia, C. molle, E. schimperi, R. natalensis, O. europaea L. subsp. cuspidataD. cinerea, A. brevispica, I. mitis, and E. tirucalli were ecologically important woody species. The majority (75%) of woody plant species had a less than 5% importance value index (IVI). The diameter class distribution of selected tree species demonstrated various patterns of population structure, implying the existence of different population dynamics among ecologically important tree species. The regeneration assessment results demonstrate that 32.35% had poor regeneration, 19.12% had good regeneration, 16.17% had fair regeneration, 8.82% lacked regeneration, and 14.08% appeared as newly regenerated species in the national park. The majority of woody species had a small population size, and some of them were found in specific habitats which need attention for conservation, and those woody species lack regeneration study soil seed bank and propagation methods for sustainable conservation.